Interactions of cyclodextrins and their derivatives with toxic organophosphorus compounds - Letort, Sophie; Balieu, Sébastien; Erb, William; Gouhier, Géraldine; Estour, François (Beilstein Journal of Organic Chemistry, 2016)
The aim of this review is to provide an update on the current use of cyclodextrins against organophosphorus compound intoxications. Organophosphorus pesticides and nerve agents play a determinant role in the inhibition of cholinesterases. The cyclic structure of cyclodextrins and their toroidal shape are perfectly suitable to design new chemical scavengers able to trap and hydrolyze the organophosphorus compounds before they reach their biological target.
Keywords: cyclodextrin; enzyme mimic; nerve agents; organophosphorus compounds; pesticides